Exploration and Practice of New Underground Excavation Method for Large Span Metro Station in Urban Area - WANG Xiang; WANG Chunkai (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] To further enhance the mechanization rate of construction and establish a new underground excavation method compatible with local environmental conditions and large-scale machinery, tailored to meet the complex requirements of urban rail transit construction, the underground excavation method for large-span metro station in urban area is studied. [Method] Based on an analysis of urban topographical and geomorphological characteristics and the challenges faced in construction within urban areas, combined with practical experiences from underground excavation projects in Guiyang Metro, conventional underground excavation methods (such as arch cover method, double-side wall heading method, and central drift method) are thoroughly examined. Relying on the Beijing Road Station project of Guiyang Rail Transit Line 3, the ′arch-pillar method′-an innovative new underground excavation method that is highly compatible with environmental requirements is proposed. [Result & Conclusion] Through research, exploration and engineering practice applications, the arch-pillar method is comprehensively and meticulously discussed in terms of design concepts, construction procedures, and key technical controls. Practical results demonstrate that compared to traditional methods, this method offers advantages such as shorter construction duration, minimal disturbance to the surrounding environment, and lower engineering costs, propelling the innovative development of large-span metro station underground excavation method.